2017
DOI: 10.1007/s11239-017-1558-1
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulation prescribing patterns in patients with cancer

Abstract: Cancer is a known hypercoagulable state that leads to an increased risk of venous thromboembolism (VTE). Low molecular weight heparin remains the preferred anticoagulant for VTE in patients with cancer over vitamin K antagonist. However, the preferred anticoagulant in prevention of stroke and systemic embolism in atrial fibrillation (AF) in patients with cancer has yet to be determined. The direct oral anticoagulants (DOACs) are increasingly being utilized; however their role in cancer has only recently been i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 31 publications
3
11
0
Order By: Relevance
“…Consistent with literature [14,15], LMWH and UFH were the most common anticoagulants used to treat CAT during an inpatient or ED visit (35.2% and 27.4%, respectively; Fig. 2).…”
Section: Discussionsupporting
confidence: 83%
“…Consistent with literature [14,15], LMWH and UFH were the most common anticoagulants used to treat CAT during an inpatient or ED visit (35.2% and 27.4%, respectively; Fig. 2).…”
Section: Discussionsupporting
confidence: 83%
“…In the recent study by Uppuluri et al [ 134 ], direct acting anticoagulants-DOACs were reported to be as safe and effective as low molecular weight heparins-LMWH in cancer subjects with thromboembolism. Similar data were reported by others [ 135 137 ]. Melloni et al [ 138 ].…”
Section: Vegfr and Hypertensionsupporting
confidence: 92%
“…A combination of antiplatelet agents and anticoagulation therapy multiplies the risk of bleeding both in the general population and in the oncological population as well. On the basis of the CHA 2 DS 2 -VASc score and HAS-BLED score, low-molecular-weight heparin or direct oral anticoagulants such as NOACs are recommended by both cardiologist and oncologist to prevent complications mentioned before in neoplastic patients [ 106 , 107 , 108 , 109 ].…”
Section: Arrhythmias Related To Neoplastic Treatmentmentioning
confidence: 99%